PENGARUH PROFITABILITAS, LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2021 - Efendi, Joni; Muhyi, Annissa; Sarpan, Sarpan; Awaludin, Muryan; Gani, Alcianno G. (JURNAL MITRA MANAJEMEN, 2024)
The goal of this study is to find out how profitability, likuidity, and capital structure influence firm value. For the period 2015-2021, the population in this study is a cement sub-sector manufacturing company registered on the Indonesia Stock Exchange. In this study, GPM. CR, and DER are used to assess profitability, likuidity, and capital structure. Meanwhile, the firm value variable is calculated using PBV. Based on the purposive sampling strategy, the number of research samples is five sompanies. The data was collected using a non-participant obsevation method. In its analysis, this study employs descriptive statistics, panel data regression analysis, the classical assumption test, and hypothesis testing. For this investigation, the Eviews 9 application was employed as a measuring tool. According to the partial test results, profitability and capital structure have a positive impact on business value, but liquidity has a negative impact. According to the simultaneous test, profitability, liquidity, and capital structure have a probability value of 0.000000 < 0.05 on company value.